Le rubriche di genere nei canzonieri della lirica galloromanza medievale (Carte Romanze, 2020)
By analysing the chansonniers of the Gallo-Romance lyric tradition, the essay aims to highlight the presence of rubrics explicitly dedicated to providing information related to the genre of the compositions they accompany. A typological analysis of these paratexts is provided, with the aim of putting in evidence the variety of functions they perform and the importance for a better knowledge of the ancient perception of the genres of medieval lyric poetry.
Keywords: Troubadour lyric poetry, chansonniers, rubrics, lyric genres.